1995
DOI: 10.1093/occmed/45.2.63
|View full text |Cite
|
Sign up to set email alerts
|

Urinary 1-hydroxypyrene: a biomarker for polycyclic aromatic hydrocarbon exposure in coal liquefaction workers

Abstract: This study was undertaken to assess the suitability of urinary 1-hydroxypyrene (1-OHPyr) as a biological marker of polycyclic aromatic hydrocarbon (PAH) exposure in coal liquefaction workers. This is believed to be the first evaluation of the method in coal liquefaction workers. Ten workers were selected from a group of 30 workers considered likely to be at risk of contamination from PAHs by virtue of their jobs. Spot urine samples were collected at the start of a work period and at the end of each work shift,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…21 difference can reach a factor of 50, from 0.5 to 25 µmol/mol creatinine. 23 The only results that differ somewhat are those of Heikkilä et al 24 : they observed a substantial increase in the 1-HOP concentration between the monday and tuesday morning samples, but found no further change over the rest of the week, as if the organism had reached its saturation point.…”
Section: Hydroxypyrenementioning
confidence: 82%
See 2 more Smart Citations
“…21 difference can reach a factor of 50, from 0.5 to 25 µmol/mol creatinine. 23 The only results that differ somewhat are those of Heikkilä et al 24 : they observed a substantial increase in the 1-HOP concentration between the monday and tuesday morning samples, but found no further change over the rest of the week, as if the organism had reached its saturation point.…”
Section: Hydroxypyrenementioning
confidence: 82%
“…59 The highest concentrations were observed among coke oven workers and in the coal industry (6 to 38.6 µmol/mol creatinine). 23,40 These data show a clear gradient in the biologic response to increased exposure to atmospheric PAHs.…”
Section: Hydroxypyrenementioning
confidence: 82%
See 1 more Smart Citation
“…Consequently, attention has been brought to the toxicokinetics of this metabolite. The time profile of 1-OHP excretion in human urine has been studied in individuals occupationally exposed to PAHs (Jongeneelen et al, 1988;Buchet et al, 1992;Van Rooij et al, 1993a;Elovaara et al, 1995;Quinlan et al, 1995aQuinlan et al, , 1995bVu-Duc & Lafontaine, 1999), as well as in volunteers exposed to pyrene (Buckley & Lioy, 1992; or PAH mixtures (Van Rooij et al, 1993b;Van Schooten et al, 1994;Brzeźnicki et al, 1997). A more detailed analysis of the kinetic behavior of 1-OHP has been conducted through experimental studies in rats acutely exposed to pyrene (Jongeneelen et al, 1985;Bouchard & Viau, 1996, 1998Bouchard et al, 1998a;Viau et al, 1999) or PAH mixtures (Jongeneelen et al, 1986;Bouchard et al, 1998b;Lipniak-Gawlik, 1998).…”
Section: Urinary Excretion Kinetics Of 1-hydroxypyrene In Rats Subchrmentioning
confidence: 99%
“…8,[11][12][13][14] However, the assay is expensive and timeconsuming. 15 Therefore, it is significant to develop a more simple and sensitive method for the determination of 1-OHP.…”
Section: Introductionmentioning
confidence: 99%